The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
37th Structure, Structural Dynamics and Materials Conference 1996
DOI: 10.2514/6.1996-1569
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of tow placed, parallel fiber, variable stiffness laminates

Abstract: It is possible to create laminates, composed of plies with spatially varying fiber orientation, which have stiffness properties that vary as a function of position. Previous work had modeled such variable stiffness laminae by taking a reference fiber path and creating subsequent paths by shifting the reference path. We introduce a method where subsequent paths are truly parallel to the reference fiber path. The primary manufacturing constraint considered in the analysis of variable-stiffness laminates was limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(65 citation statements)
references
References 2 publications
0
61
0
Order By: Relevance
“…The angle of the reference fibre path, ✓, is a linear function of the x-coordinate and, in order to define the other fibre paths, this reference fibre path is shifted in y-direction [2].…”
Section: Eigenvalue Problem Of Vscl Plates With Piston Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The angle of the reference fibre path, ✓, is a linear function of the x-coordinate and, in order to define the other fibre paths, this reference fibre path is shifted in y-direction [2].…”
Section: Eigenvalue Problem Of Vscl Plates With Piston Theorymentioning
confidence: 99%
“…These two techniques alter the final shape of the design by occupying more space and increasing the weight. The variable stiffness concept using curvilinear fibres [1,2,3] can propose a panel with different, and under-controlled stiffness. This concept suggests to rotate fibre orientation in a region with high stress.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally the choice of these lay-ups was motivated by manufacturability, while nowadays lay-ups with changing or even non-conventional fiber angles are avoided because of the lack of allowables. However, research on composites with a varying in-plane fiber orientation has shown that variable stiffness can be beneficial for structural performance [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], because variable-stiffness laminates are able to redistribute the loading more efficiently than constant-stiffness laminates. In most cases curvilinear fiber paths manufactured by tow placement are used to construct the variable-stiffness laminates [4, 5, 9-11, 15, 18-20].…”
Section: Introductionmentioning
confidence: 99%
“…In-depth study of rectangular panels with curvilinear fiber paths, termed variable stiffness panels, was performed in a series of publications by Gürdal et al [16][17][18] . These panels are manufactured by either shifting or parallel fiber path generation starting from a linearly varying orientation base curve.…”
Section: Literature Reviewmentioning
confidence: 99%